Infection and Killing of Multiple Myeloma by Adenoviruses - Senac, Julien S. (Mary Ann Liebert, Inc., 2010)
Oncolytic virotherapy makes use of the natural ability of viruses to infect and kill cancer cells. Adenovirus serotype 5 (Ad5) has been approved for use in humans as a therapy for solid cancers. In this study, we have tested whether Ad5 and low-seroprevalence adenoviruses can be used as oncolytics for multiple myeloma (MM). We show that Ad5 productively infects most myeloma cell lines, replicates to various degrees, and mediates oncolytic cell killing in vitro and in vivo. Comparison of Ad5 with low-seroprevalence Ads on primary marrow samples from MM patients revealed striking differences in the abilities of different adenoviral serotypes to kill normal CD138(–) cells and CD138(+) MM cells. Ad5 and Ad6 from species C and Ad26 and Ad48 from species D all mediated killing of CD138(+) cells with low-level killing of CD138(–) cells. In contrast, Ad11, Ad35, Ad40, and Ad41 mediated weak oncolytic effects in all of the cells. Comparison of cell binding, cell entry, and replication revealed that Ad11 and Ad35 bound MM cells 10 to 100 times better than other serotypes. However, after this efficient interaction, Ad11 and Ad35 viral DNA was not replicated and cell killing did not occur. In contrast, Ad5, Ad6, Ad26, and Ad48 all replicated 10- to 100-fold in MM cells and this correlated with cell killing. These data suggest that Ad5 and other low-seroprevalence adenoviruses may have utility as oncolytic agents against MM and other hematologic malignancies.